ANALISIS PEMBELAJARAN TERDIFERENSIASI PADA PROSES PELAJARAN MATEMATIKA SISWA KELAS IV DI SDN KEMANGGISAN 10 PAGI - Ida Maria Mabel; Mujazi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Ida Maria Mabel, 2024: Analysis of Differentiated Learning on Learning Outcomes of Class IVA Students at SDN Kemanggisan 10 Pagi. Thesis. PGSD Study Program, Faculty of Teacher Training and Education, Esa Unggul University Jakarta. This research is a descriptive qualitative research. The research was conducted to analyze mathematics learning outcomes through the implementation of differentiated learning for IVA grade students at SDN Kemanggisan 10 Pagi. The subjects in this study were 28 students of class IVA, the class teacher, and the principal. The data collected on techniques used in the study were observation, interview, and documentation. Data analysis techniques in the study were carried out through interactive analysis, which reduced data, presented, and verified it. The results obtained from the implementation of the research are (1) changes in students in terms of activeness, (2) self-confidence, (3) students feel comfortable when learning, (4) learning becomes more fun, (5) making it easier for students to understand the material taught by the teacher, (6) students become more independent, (7) work together, (8) get better grades in math subjects than before, (9) critical reasoning, (10) creativity, and (11) collaboration between friends. Based on the results of this study, it can be concluded that the implementation of differentiated learning in mathematics subjects in class IVA can provide changes from the aspect of soft skills and hard skills.